Localised manual therapy treatment has a preferential effect on the kinematics of the targeted motion segment. (December 2021) - Tuttle, Neil; Evans, Kerrie; Sperotto dos Santos Rocha, Clarice
Abstract: Aim: An observational cohort study to determine whether localised manual therapy results in a preferential increase in mobility of the targeted motion segment. Method: Eighteen participants with mechanical neck pain had three MRIs of their cervical spine. The first two were taken prior to treatment in neutral and at the end of active rotation in their more limited rotation. Participants received localised manual therapy targeting a motion segment deemed to be relevant to their presentation until either their range increased by > 10° or 8 min, whichever came first. A third MRI was performed immediately after treatment with their head in the same rotated position as pre-treatment. In the images, each vertebra was segmented using a semi-automated process. Movement between neutral and rotated positions was calculated as Euler angles and distance of facet translations for each motion segment. Results: Rotation and lateral flexion at the targeted location increased by 40% (mean 0.86° (CI: 0.24–1.48) and 15% (mean 0.52° (CI: 0.17–1.21) respectively with only the CIs for rotation not containing zero. The mean changes for the non-targeted locations were less than 0.1° for each axis and all CIs contained zero. Facet translations at the targeted location increased by 25% (0.419 mm) and decreased by >4% (>0.01 mm) at the untreated locations but the wide CIs both contained zero. Conclusion: Localised manual therapy seems to have a preferential effect on mobility of the targeted motion segment. The findings support considering segmental dysfunction in clinical reasoning and the use of specifically targeted manual therapy interventions. Highlights: Spinal manual therapy preferentially effects kinematics at the targeted level. This study provides support for specifically targeted manual therapy treatment. Findings are consistent with localised changes in PA passive stiffness.